2013
DOI: 10.1002/2013jb010497
|View full text |Cite
|
Sign up to set email alerts
|

Hydration adjacent to a deeply subducting slab: The roles of nominally anhydrous minerals and migrating fluids

Abstract: [1] Subduction-related transport of water into the mantle has significant dynamical and geochemical implications. Dehydration of hydrous phases within the slab can introduce water into the transition zone and lower mantle, potentially hydrating nominally anhydrous minerals (NAM) and impacting the viscosity and density structure of the mantle over a wide area. We present models of fluid transport and mantle hydration in the vicinity of a deeply subducting slab, focusing on the fate of water released by deep deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 128 publications
(206 reference statements)
1
17
1
Order By: Relevance
“…The values are consistent with those estimated in the models of Wilson et al [] with relatively low and moderate fluid mobilities. In nature, fluid velocity might be at least 1 order of magnitude higher than the subduction velocity [ Wilson et al , ; Hebert and Montési , ].…”
Section: Discussionmentioning
confidence: 99%
“…The values are consistent with those estimated in the models of Wilson et al [] with relatively low and moderate fluid mobilities. In nature, fluid velocity might be at least 1 order of magnitude higher than the subduction velocity [ Wilson et al , ; Hebert and Montési , ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous workers have stressed the importance of water incorporation into NAMs in the mantle wedge as an effective way to transport water into the deep Earth's interior (Hebert & Montési, ; Horiuchi & Iwamori, ; Iwamori, ). Hydrous defects are dominated by Si vacancies under the relevant conditions for the mantle wedge ( T > 900°C and P > 3 GPa, Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Our model approach is essentially instantaneous and has an isoviscous mantle, thus implying that our models do not capture potential increases in the mantle's resistance to slab sinking in and below the transition zone. However, it has been shown that viscosity in the transition zone drops due to high water content (Hebert and Montési, 2013), and high resistance to upper mantle slabs may not be expected at these depths. Resistance to slab sinking will increase at some depth below the transition zone, depending on the viscosity profile of the mantle.…”
Section: Numerical Model Limitations Summarymentioning
confidence: 99%